The 10B based jalousie neutron detector: an alternative for 3He filled position sensitive counter tubes - Henske, Markus; Klein, Martin; Köhli, Markus; Lennert, Peter; Modzel, Gerd; Schmidt, Ulrich (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
Over the last decades 3He filled proportional counter tubes were the working horse employed to serve as neutron counters especially in cases where large area coverage was required. Today the lack of 3He demands the development of an alternative technology. Here we present a prototype neutron detector that is based on a concept with solid 10B as neutron converter and aims for large area neutron detection applications. We report on first experimental results obtained with this prototype to demonstrate the feasibility and operational readiness of our concept.